Acetylation of α-tubulin restores endothelial cell injury and blood–brain barrier disruption after intracerebral hemorrhage in mice - Xuejiao Lei; Eryi Sun; Xufang Ru; Yulian Quan; Xuezhu Chen; Qian Zhang; Yougling Lu; Qianying Huang; Yujie Chen; Wenyan Li; Hua Feng; Yang Yang; et al. (Experimental and Molecular Medicine)
Abstract Damage to endothelial cells (ECs) is a key factor in blood–brain barrier (BBB) disruption after intracerebral hemorrhage (ICH). While microtubules are essential for EC structure, their role in BBB injury remains unclear. Here we investigated the role of acetylated α-tubulin (α-Ac-Tub) in BBB integration after ICH. Using an autologous blood injection model in the striatum, we showed that the expression of α-Ac-Tub and MEC17, an α-tubulin acetyltransferase, significantly decreased along the vessels around the hematoma after ICH. Conditional MEC17 knockout in ECs further reduced α-Ac-Tub levels and exacerbated BBB leakage, brain edema, hematoma expansion, inflammation and motor dysfunction. Conversely, selective α-Ac-Tub upregulation in ECs via intravenous delivery of AAV-BI30-MEC17-GFP alleviated BBB dysfunction and improved motor recovery. Similarly, the HDAC6 inhibitor tubastatin A enhanced α-Ac-Tub levels, mitigating BBB damage and neurological deficits. Mechanistically, α-Ac-Tub deficiency in ECs reduced tight junction proteins (ZO-1 and Claudin5) and increased F-actin stress fibers through RhoA activation. Together, our findings highlighted α-Ac-Tub as a therapeutic target for restoring BBB function and reducing brain injury after ICH.